2009
DOI: 10.1016/j.pharmthera.2009.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological profiles of alpha 2 adrenergic receptor agonists identified using genetically altered mice and isobolographic analysis

Abstract: Endogenous, descending noradrenergic fibers convey powerful analgesic control over spinal afferent circuitry mediating the rostrad transmission of pain signals. These fibers target alpha 2 adrenergic receptors (α 2 ARs) on both primary afferent terminals and secondary neurons, and their activation mediates substantial inhibitory control over this transmission, rivaling that of opioid receptors which share similar a similar pattern of distribution. The terminals of primary afferent nociceptive neurons and secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(70 citation statements)
references
References 177 publications
(302 reference statements)
1
68
0
1
Order By: Relevance
“…Dex demonstrates peripheral and centrally mediated antinociception via receptor activation in the dorsal horn and the locus coeruleus. 25,26 Dex administered before the end of surgery reduced morphine requirement in the immediate postoperative period in adult patients undergoing major abdominal or orthopedic procedures. 27 Patel et al 14 also reported that an intraoperative infusion of Dex significantly reduced the postoperative opioid requirement in children.…”
Section: Discussionmentioning
confidence: 97%
“…Dex demonstrates peripheral and centrally mediated antinociception via receptor activation in the dorsal horn and the locus coeruleus. 25,26 Dex administered before the end of surgery reduced morphine requirement in the immediate postoperative period in adult patients undergoing major abdominal or orthopedic procedures. 27 Patel et al 14 also reported that an intraoperative infusion of Dex significantly reduced the postoperative opioid requirement in children.…”
Section: Discussionmentioning
confidence: 97%
“…Activation of ␣ 2A -receptors could be linked with bradycardia and hypotension (MacMillan et al, 1996), sedation (Lakhlani et al, 1997;Gilsbach et al, 2009), and consolidation of working memory (Wang et al, 2007). Hypothermia and antinociception induced by ␣ 2 -agonists depend primarily on functional ␣ 2A -adrenoceptors (Stone et al, 1997;Gilsbach et al, 2009), but other subtypes may also contribute to these pharmacological effects under certain conditions (Sallinen et al, 1997;Fairbanks et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Brain and spinal alpha 2 receptor activation inhibit neuronal firing, which leads to hypo tension, bradycardia, sedation and analgesia. Apart from action in nervous system, extraneuronal alpha 2 activation leads to decrease in salivation and secretions, decrease gastric motility, inhibit renin release, increased glomerular filtration rate; decreased intraocular pressure and decrease insulin secretion from the pancreas [18,19]. There are various sub classification of alpha 2 receptor, alpha 2 A, B and C [16].…”
Section: Pharmacodynamic Of Dexmedetomidinementioning
confidence: 99%
“…Apart from prolonging analgesia, it has been used for prevention and treatment of shivering [14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%